2014
DOI: 10.1007/s10903-014-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Risk Factors for Postpartum Depression in Refugee and Immigrant Women: Are Current Screening Practices Adequate?

Abstract: Currently little is known of postpartum depression (PPD) screening and referral for refugee and immigrant women in Northern New England where the foreign born population has been rapidly expanding in the past decade. Research on PPD has focused largely on the general population leaving a large gap in our understanding of PPD in this vulnerable group. A retrospective chart review was conducted from a tertiary medical center with 1,160 births per year. Total sample n = 126, 28 % scored at risk for PPD. 39 % of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 27 publications
1
58
0
Order By: Relevance
“…Studies also found that accessing interpreters was not always possible (Thompson ; Tobin et al . ). In Tobin et al .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Studies also found that accessing interpreters was not always possible (Thompson ; Tobin et al . ). In Tobin et al .…”
Section: Resultsmentioning
confidence: 97%
“…Tobin et al . () reported that if the tool is not self‐administered, it might influence scores, thereby influencing the accuracy of the tool. Tobin et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We argue that the theme ‘ Making sense of my feelings ” articulates the multiple factors that challenge migrant women when they are becoming mothers in a new country. Contextual factors (no support from family and community, migration status, socioeconomic status, gender roles) explicated in this theme are risk factors for the development of PND symptoms in explanatory models of PND [49] and are also factors that mediate help seeking behaviours[50, 51]. Furthermore, the theme ‘ What I need to address my feelings ’, alerts us to the limitations of current health services in addressing women’s needs and identifies how this can be remedied.…”
Section: Discussionmentioning
confidence: 99%